2007
DOI: 10.1038/nsmb1316
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK signaling regulates recruitment of Ash2L-containing methyltransferase complexes to specific genes during differentiation

Abstract: Cell-specific patterns of gene expression are established through the antagonistic functions of trithorax group (TrxG) and Polycomb group (PcG) proteins. Several muscle-specific genes have previously been shown to be epigenetically marked for repression by PcG proteins in muscle progenitor cells. Here we demonstrate that these developmentally regulated genes become epigenetically marked for gene expression (trimethylated on histone H3 Lys4, H3K4me3) during muscle differentiation through specific recruitment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
214
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(223 citation statements)
references
References 41 publications
7
214
0
Order By: Relevance
“…This is consistent with the concept that E2F1 phosphorylation by p38, together with its export from the nucleus and degradation, is essential for proper keratinocyte differentiation. In this regard, p38 also plays a positive regulatory role in muscle differentiation, through phosphorylation and modulation of the Mef2 transcription factor (Rampalli et al, 2007), suggesting that p38 activity most likely plays a broad role in differentiation in a variety of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the concept that E2F1 phosphorylation by p38, together with its export from the nucleus and degradation, is essential for proper keratinocyte differentiation. In this regard, p38 also plays a positive regulatory role in muscle differentiation, through phosphorylation and modulation of the Mef2 transcription factor (Rampalli et al, 2007), suggesting that p38 activity most likely plays a broad role in differentiation in a variety of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…pathway through upregulation of the JNK phosphatase MKP-1 [25]. More recently, p38 has been linked to the epigenetic regulation of myogenesis through both repressive [26,27] and activating [28] histone modifications. p38c acts in opposition to p38a, blocking premature differentiation through induction of a repressive MyoD transcriptional complex [26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MyoD binding does not always correlate with transcriptional activation (9,15). MyoD, with the help of other transcription factors and/or cofactors, can bind to E-box sites prior to transcriptional activation (25,26). Recently, it was shown that MyoD binds to many of the skeletal muscle-specific genes during the course of differentiation (24).…”
mentioning
confidence: 99%